2008
DOI: 10.1093/nar/gkn108
|View full text |Cite
|
Sign up to set email alerts
|

A role for Caf1 in mRNA deadenylation and decay in trypanosomes and human cells

Abstract: The eukaryotic Ccr4/Caf1/Not complex is involved in deadenylation of mRNAs. The Caf1 and Ccr4 subunits both potentially have deadenylating enzyme activity. We investigate here the roles of Ccr4 and Caf1 in deadenylation in two organisms that separated early in eukaryotic evolution: humans and trypanosomes. In Trypanosoma brucei, we found a complex containing CAF1, NOT1, NOT2 and NOT5, DHH1 and a possible homologue of Caf130; no homologue of Ccr4 was found. Trypanosome CAF1 has deadenylation activity, and is es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
170
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(182 citation statements)
references
References 70 publications
9
170
2
1
Order By: Relevance
“…Several studies revealed a biphasic decay pattern for EP1 mRNA in bloodstream forms and identified the nucleases involved [27][28][29]46]. In one of our experiments, a decay pattern reminiscent of biphasic decay kinetics was found for GPEET mRNA in late PF (with only 0.4% GPEET-positive cells) (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…Several studies revealed a biphasic decay pattern for EP1 mRNA in bloodstream forms and identified the nucleases involved [27][28][29]46]. In one of our experiments, a decay pattern reminiscent of biphasic decay kinetics was found for GPEET mRNA in late PF (with only 0.4% GPEET-positive cells) (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…Knockdown of CAF1 by RNA interference (RNAi) has been shown to impair the deadenylation and decay of an ARE-containing ␤-globin mRNA (25,26). In contrast, CCR4 depletion has been reported to have no effect on deadenylation of an ARE reporter mRNA (26). Mammalian cells also contain another, predominantly nuclear enzyme, poly(A) ribonuclease (PARN) (27).…”
mentioning
confidence: 99%
“…Analysis of CAF1 in Caenorhabditis elegans using RNAi and deletion alleles demonstrates that CAF1 is essential for embryonic and larval development (Molin and Puisieux, 2005). Additionally, CAF1 is required for normal growth of trypanosomes (Schwede et al, 2008). Finally, mice lacking CAF1 are sterile (Nakamura et al, 2004).…”
mentioning
confidence: 99%